Pemahaman Pendidikan Agama Islam dan Kesadaran Menunaikan Sholat - Nanang Faisol Hadi; Umar Fauzan; Noor Malihah (SAP (Susunan Artikel Pendidikan), 2022)
The constitutions that are directly related to education in this country have clearly outlined the ideal of an education. The importance of education for human life as carriers and actors of civilization cannot be avoided, because it is a collection of experience-based abilities and behavior development processes. The stage that is no less important in education is understanding, that is the ability to capture the meaning and significance of something being studied. While the goal is awareness of learning on knowledge and awareness to apply what is learned in their lives. This also applies in understanding Islamic religious education, which also requires awareness to apply it in daily life. The purpose of this study was to analyze the effect of understanding Islamic religious education on the awareness of students in performing prayers. This type of research is quantitative with the determination of respondents proportionate stratified random sampling 15%. The study was conducted in September-November 2021 (1st semester of the 2021/2022). The validity of the instrument is known by the Pearson Product Moment (r count), then the significance test is calculated. Testing the reliability of the questionnaire following Akdon's opinion, calculating (score, correlation, reliability, r table). To analyze the data used SPSS program. The final results in this study inform the significance of the influence and contribution of understanding Islamic religious education (simultaneously) on the awareness of students at SMA Negeri 1 Penajam Paser Utara in performing prayers of 51.7%. This means that the level of awareness of students performing prayers that can be given by the influence of understanding Islamic religious education (simultaneously) is 51.7%. The remaining 48.3% is explained by other factors not examined in this study.